Protein–RNA and protein–glycan recognitions in light of amino acid codes - Nahalka, Jozef; Hrabarova, Eva; Talafova, Klaudia (Biochimica et biophysica acta, 2015)
RNA-binding proteins, in cooperation with non-coding RNAs, play important roles in post-transcriptional regulation. Non-coding micro-RNAs control information flow from the genome to the glycome by interacting with glycan-synthesis enzymes. Glycan-binding proteins read the cell surface and cytoplasmic glycome and transfer signals back to the nucleus. The profiling of the protein–RNA and protein–glycan interactomes is of significant medicinal importance. This review discusses the state-of-the-art research in the protein–RNA and protein–glycan recognition fields and proposes the application of amino acid codes in profiling and programming the interactomes. The deciphered PUF–RNA and PPR–RNA amino acid recognition codes can be explained by the protein–RNA amino acid recognition hypothesis based on the genetic code. The tripartite amino acid code is also involved in protein–glycan interactions. At present, the results indicate that a system of four codons (“gnc”, where n=g — guanine, c — cytosine, u — uracil or a — adenine) and four amino acids (G — glycine, A — alanine, V — valine, D — aspartic acid) could be the original genetic code that imprinted “rules” into both recognition processes. Amino acid recognition codes have provocative potential in the profiling and programming of the protein–RNA and protein–glycan interactomes. The profiling and even programming of the interactomes will play significant roles in diagnostics and the development of therapeutic procedures against cancer and neurodegenerative, developmental and other diseases. •Recent advances in RNA and glycan recognition by proteins•We have discussed how protein–RNA and protein–glycan “interactomes” contribute to genetic information flow.•We have explored a variety of biological systems in order to deduce some general rules.